Significant learning experiences to revolutionize the world of teaching - Gómez Navarro, María Victoria
Education in Colombia has had an aging process due to lack of memory and systematization of significant learning experiences in different public and private training centers. The qualitative research of participatory and explanatory type will allow to determine, from various case studies, how significant learning experiences can revolutionize the world of teaching without allowing it to age, but oxygenating it every day, contributing valuable experiences to the teaching-learning process. Can a significant learning experience rescue the student from the academic ostracism into which he or she has fallen?